The Representation of Malay Leader in Malay Song Datuk Laksemana - Essy Syam; Ulul Azmi; Qori Islami Aris (Journal of Social Transformation and Regional Development, 2021)
This writing analyzes a lyric of a Malay song entitled Datuk Laksemana by focusing on how a Malay leader is represented. This is a descriptive analysis which describes the phenomenon of the representations of Malay leader in that lyric. The result shows that the Malay leader is mostly represented by positive representation. Anyway, there is also less positive representation which is caused by the perception believed in the era of Malay kingdoms.